Microfiber loop resonator for relative humidity and formaldehyde sensing / Sana Sualaiman Hamid Al-asaadi - Sana Sulaiman , Hamid Al-asaadi (2018)
Recently, optical micro-resonators (OMRs) gained noticeable importance due to the bright potential of using them in vital applications, and the simplest and most practical type of micro-fiber resonators are Micro-fiber Loop Resonators (MLRs) because of their simple fabrication process and high sensitivity. In this research, the sensitivity of the optical Micro-fiber Loop Resonators (MLRs) to relative humidity (RH) and Formaldehyde liquid is tested. The MLR is fabricated from the silica optical fiber (SMF-28) by a process of tapering to reduce its waist diameter using a flame brushing technique. The tapered fiber is manually twisted to create the MLR and placed on a movable glass stage. Two experiments are done to test the sensitivity for various fiber diameters based MLRs. The first one, is the test of the MLRs RH sensitivity using fibers with different diameters (3 ?m, 4 ?m, 5 ?m and 7 ?m). Also, the Straight micro-Fiber (SmF) RH sensitivity is tested for comparison purposes. Initially, the whispering gallery modes (WGMs) effect was observed in the MLR. Transmission mode spectra are examined to determine the number of resonated wavelengths and quality factor (Q-factor). The observed Q-factor for the MLRs is equal to > 105 which is good for sensing applications. By changing the RH and observing the MLR resonating behavior, it was concluded that the significant resonating response clearly occurs when the RH value ranges from 35% to 85%. All MLRs show higher stability than SmF when tested for a period of 600 seconds. As the RH increases, the sensitivity also increases, and it is 14 times for MLR based on 7 ?m diameter fibers more than the value for the SmF. The output power decreases form -55.04 dBm to -65 dBm when the RH increase from 35% to 85%. The MLR linearity is found to be 98.80% and its resolution is 0.0344%. The second experiment, is the testing of the MLR Formaldehyde sensitivity using fiber with (7 ?m diameter) and Straight micro-Fiber. The Formaldehyde concentration used in this experiment range from 0% - 5%. The effect of WGMs was observed in the MLR. By examining the Transmission mode spectra, the MLR Q-factor was determined to be > 105 . The MLR shows higher stability for all the formaldehyde concentration levels than the SmF for the 600 seconds testing time. the output power decreases from -36.26 dBm to -19.04 dBm with the increase of the formaldehyde concentration level, A high linearity value of 98.22% was calculated and the good sensitivity level of 0.0259% was observed.